The Physiological Aspects of Exercise-Induced Adaptation in the Cardiovascular System - Abdulla Ahmad (Al-Anbar Medical Journal)
Low exercise and a sedentary lifestyle are independently attributed to a rise in the level of morbidity and mortality. In the past four decades, explosive progress in knowledge and application has been made in the field of exercise physiology. Exercise can be regarded as an evolutionary stimulus for ameliorating human cardiovascular health. Several studies showed that heart attack patients who implement a formal exercise program can have a reduced death rate of 20-25%. The cardiovascular beneficial effects of regular physical activity are suggested mainly due to the exercise-induced changes in different cardiovascular risk factors such as obesity, dyslipidemia, and high blood pressure. We conducted an extensive literature search on various electronic databases such as PubMed, Science Direct, Scopus, and Web of Science. This review aimed at providing further advancement of our understanding of how different cardiovascular aspects can be modulated by exercise which could be considered as novel therapeutic strategies to prevent or treat different cardiovascular disorders. The present knowledge regarding exercise-induced cardiovascular adaptation, including processes and bioactive substances, has been improved, but many molecular/cellular aspects remain to be elucidated.